Comparison of total antioxidant capacity of salivary, capillary and venous samplings: interest of the salivary total antioxidant capacity on triathletes during training season - Youssef, H.; Groussard, C.; Machefer, G.; Minella, O.; Couillard, A.; Knight, J.; Gratas-Delamarche, A. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: Total antioxidant capacity (TAC) is an essential parameter to watch over defense system of athletes exposed to an oxidant stress during intensive periods of training. To control this parameter throughout the training period, repetitive biological samples are required. The TAC is usually investigated in venous blood which needs invasive withdrawings. Thus, we proposed to find alternatives to venous blood analysis by venepuncture, which is invasive, stressful and not allow a regular follow-up on athletes during annual training season. Methods: We measured capillary and salivary TAC in 65 physically active subjects at rest and compared them to the venous TAC. We followed the evolution of venous and salivary TAC in 7 triathletes throughout an annual training period (March and June) corresponding to two different types of training. Results: There was a good correlation between plasma venous and capillary TAC values (r=0.77; P<0.0001), but salivary TAC were significantly lower than the plasma ones and did not correlate. Venous and saliva TAC of triathletes were significantly higher in March compared to June. The variations of plasma and salivary TAC between the two periods of training were correlated (r=0.96; P<0.01). Conclusion: The capillary sampling can replace the venous one for TAC evaluation in routine assays for the follow-up of athletes. Even if saliva TAC did not reflect plasma TAC, it could be used in the follow-up of athletes since a strong correlation is found between the variation of saliva and plasma TAC during the training season